The Modal Particles in the Storybook 原我这么棒 Yuánlái Wύ Zhème Bàng By Li Huizhen Partikel Modalitas dalam Buku Cerita 原来我这么棒 Yuánlái Wǒ Zhème Bàng Karya Li Huizhen - Yayan Yunita Handayani; Yulie Neila Chandra (Bambuti, 2020)
Particles in Mandarin can be divided into three kinds, namely structural, aspectual, and modality or modal particles. The particles have their own functions, as well as having grammatical meanings. This article discusses the particles of modality in the children's storybook entitled原我这么棒(Yuánlái Wύ Zhème Bàng) 'I'm So Great' by Li Huizhen. Particles of modality are widely used in the context of the conversation in the storybook, namely 啊 a, 吧 ba, 啦la, 了le, 啰luo, 吗ma, 嘛ma, 哪na, 呢ne, 呀ya, 哟yo. Through distributional analysis methods, as well as with the technique of evaporation and transfer analysis, the modality particles can be matched with phatic particles in Indonesian, such as 'ya', 'lah', 'sih', 'lho', and 'dong' which are generally located behind sentences, and some behind clauses. However, the meaning of the particles is uncertain and unsteady because each depends on the context of the sentence or the meaning of the sentence. The presence of modality particles in a sentence can change the meaning of a sentence, its type of sentence, or its language function.